Entre inconformismo e reformismo;; - Furtado, Celso (Estudos Avançados, 1990)
This is a paper-synthesis where the author summarizes his theory of development and underdevelopment. Some basic ideas are here presented: the economic theory of development must start wiht the study of history; underdevelopment is a specific historical and economical phenomenon, that cannot be thought in terms of linear stages of history; this historical phenomenon must be studied in structural terms, relating the historic and the economic aspects; the basic characteristic of underdevelopment is the dependency relation, expressed in the center-periphery system; in the study of development the basic concept to start with is the concept of social surplus, its forms of appropriation and utilization. The paper ends with an analysis of the frustrations of a reformist. Protectionism, that was justifiable in a first phase of industrialization, was maintained too long in Latin America; in a second phase, an active economic policy for exports was necessary. On the other hand the populist risk was always present, while the real social problems related to a high level of income concentration were not solved.